General practitioner and nurse prescriber experiences of prescribing antibiotics for respiratory tract infections in UK primary care out-of-hours services (the UNITE study). (27th November 2017) - Williams, S J; Halls, A V; Tonkin-Crine, S; Moore, M V; Latter, S E; Little, P; Eyles, C; Postle, K; Leydon, G M
Abstract: Background: Interventions are needed to reduce unnecessary antibiotic prescribing for respiratory tract infections (RTIs). Although community antibiotic prescribing appears to be decreasing in the UK, figures for out-of-hours (OOH) prescribing have substantially increased. Understanding the factors influencing prescribing in OOH and any perceived differences between general practitioner (GP) and nurse prescriber (NP) prescribing habits may enable the development of tailored interventions promoting optimal prescribing in this setting. Objectives: To explore UK GP and NP views on and experiences of prescribing antibiotics for RTIs in primary care OOH services. Methods: Thirty semi-structured interviews were conducted with GPs and NPs working in primary care OOH services. Inductive thematic analysis was used to analyse data. Results: The research shows that factors particular to OOH influence antibiotic prescribing, including a lack of patient follow-up, access to patient GP records, consultation time, working contracts and implementation of feedback, audit and supervision. NPs reported perceptions of greater accountability for their prescribing compared with GPs and reported they had longer consultations during which they were able to discuss decisions with patients. Participants agreed that more complex cases should be seen by GPs and highlighted the importance of consistency of decision making, illness explanations to patients as well as a perception that differences in clinical training influence communication with patients and antibiotic prescribing decisions. Conclusions: Environmental and social factors in OOH services and a mixed healthcare workforce provide unique influences on antibiotic prescribing for RTIs, which would need to be considered in tailoring interventions that promote prudent antibiotic prescribing in OOH services.